Pemanfaatan Teknologi Virtual Tour Reality Menggunakan Metode Image Stitching dan Seam Carving pada Desa Wisata Tawangmangu sebagai Media Promosi Inovatif - Putri, Astrid Novita; Buana, Pratama Angga; Adinugroho, Suryo; Wardhani, Anindya Khrisna (Jurnal Pengabdian Masyarakat Teknologi dan Pendidikan (MANTAP), 2024)
Tawangmangu Tourism Village in Central Java offers a wide range of attractions, including flower gardens, cultural traditions, and captivating natural beauty. However, challenges in adopting modern technology-based promotion limit its appeal to tourists. This study aims to develop a promotional medium based on a Virtual Tour Reality application utilizing Image Stitching and Seam Carving technologies. These technologies enable comprehensive visualization of destinations through 360° panoramic images, accessible on any internet-connected device.The Multimedia Development Life Cycle (MDLC) method was applied in the application development process, including data collection, design, production, testing, and distribution. Data was gathered through interviews with village tourism managers to analyze needs and provide relevant solutions. The study produced 151 panoramic images and a web-based virtual tour application that effectively attracts tourists with interactive and informative visualizations. The implementation of this technology not only enhances the accessibility of tourism information but also promotes the potential of Tawangmangu Tourism Village on a global scale. These results mark a significant first step toward integrating advanced technology into destination marketing strategies.